Should the Principles of Digital Development be Agile? - and ICTworks (2016)
Recently, Abt Associates endorsed the “Principles of Digital Development.” These nine principles have been widely adopted by international development funders and practitioners to absorb and disseminate technology best practices in the field of international development. More than 50 organizations ranging from various offices in the United Nations and the U.S. Agency for International Development (USAID) down to niche technology providers have endorsed the principles. The principles are aimed at moving the field away from a disconnected series of technology pilots, each of which are largely ad hoc and duplicate many of the same lessons, and toward scalability and sustainability. Ann Mei Chang, the Executive Director of the U.S. Global Development Lab at USAID in her foreword to the recent report “From Principle to Practice: Implementing the Principles for Digital Development”, characterized the problem that these principles are trying to address as follows: “Pilots have failed to move